Linear and nonlinear optical waveguiding in bio-inspired peptide nanotubes. (15th January 2016) - Handelman, Amir; Apter, Boris; Turko, Nir; Rosenman, Gil
Graphical abstract: Abstract: Unique linear and nonlinear optical properties of bioinspired peptide nanostructures such as wideband transparency and high second-order nonlinear optical response, combined with elongated tubular shape of variable size and rapid self-assembly fabrication process, make them promising for diverse bio-nano-photonic applications. This new generation of nanomaterials of biological origin possess physical properties similar to those of biological structures. Here, we focus on new specific functionality of ultrashort peptide nanotubes to guide light at fundamental and second-harmonic generation (SHG) frequency in horizontal and vertical peptide nanotubes configurations. Conducted simulations and experimental data show that these self-assembled linear and nonlinear optical bio-waveguides provide strong optical power confinement factor, demonstrate pronounced directionality of SHG and high conversion efficiency of SHG ∼10 −5 . Our study gives new insight on physics of light propagation in nanostructures of biological origin and opens the avenue towards new and unexpected applications of these waveguiding effects in bio-nanomaterials both for biomedical nonlinear microscopy imaging recognition and development of novel integrated nanophotonic devices.